Penerapan Prinsip Good Governance Dalam Pelayanan Publik (Studi Pada Mall Pelayanan Publik Kabupaten Konawe) - Rahmaryah, Sitti Rahmaryah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
This study aims to find out and examine how the application of the principles of goodgovernance has been implemented properly or not, this study used qualitative research, whilethe number of informants in this study were 7 people. Data collection techniques usinginterviews, observation, and documentation. Data analysis techniques using data reductionsteps, data presentation, and drawing conclusions. The results of the study show that theapplication of the principles of good governance has not been implemented properly wherethere is one indicator that has not been implemented in the Konawe district public servicemall office. This can be seen from indicator (1) the accountability indicator has beenimplemented properly where the head of the licensing service and office employees theKonawe district public service mall has been responsible for the problems that have arisen.(2) transparency indicators have been implemented properly where employees do not chargeservice fees. (3) indicators of the rule of law have not been fully implemented properly wherepublic service mall office employees use an insider system. (4) inhibiting factors inimplementing the principles of good governance, namely SOPs that are still being compiledtemporarily and data storage facilities that are still insufficient. (5) supporting factors inimplementing the principles of good governance, namely adequate facilities for service usercommunities, the alertness and responsiveness of employees in helping the community, andfinally the design of a public service mall that facilitates people with physical limitationsKeywords : good Governance, Service